LANDSCAPE IN THE HOUSING ESTATES OF THE CZECH REPUBLIC IN 1960s-1980s - Magni, Anna (European Scientific Journal, ESJ, 2014)
Mass housing estates of the second half of the 20th century represent a poorly described and appraised topic of recent history. Mainly professionals overlook their garden design related aspect. It seems unbuilt areas within them were neglected by their authors; still, they represent an essential change in the urban structure in the 20th century and the rising significance of elements representing nature in urbanized environments. The present text focuses on housing estates in the Czech Republic that were built between the 1960s and 1989, especially their garden design related and landscape related aspects. First, circumstances of post-war building of mass housing and the role of modernist theories are introduced. Second, the development of forms of public areas in specific conditions of socialist central planning is observed. Our exploration concentrates on significant projects presented in the press of the time as well as housing estates that did not stand out from the average. The results, which we are presenting, are an overview of particular types of public spaces within mass housing estates with their basic characteristics and a definition of the roles of vegetation and other garden design means related to housing. In conclusion, we formulate a general development direction which the relation between landscape and housing took, as we can observe it in the example of housing estates of the second half of the 20th century.